Designing ultra-fast all-optical full-subtractor using the photonic crystal structure - Pakrai, Forogh; Soroosh, Mohammad; Ganji, Jabbar (Oficyna Wydawnicza Politechniki Wrocławskiej, 2023)
In this paper, a photonic crystal-based structure for an all-optical full-subtractor has been proposed. The structure includes six nonlinear resonant rings to transmit the incoming optical waves toward the output ports. Using the different radii for nonlinear rods made the possibility of the dropping operation for different amounts of optical intensities. The nonlinear rods are made of a doped-glass with an optical Kerr coefficient of 10–15 m2/ W. To calculate the components of the optical waves throughout the structure, the finite-difference time-domain method has been used. The simulation results prove the correct functionality of the proposed structure. Besides, the maximum rise time of the device is equal to 2 ps. The contrast ratio and the area of the structure are around 8.08 dB and 2790 µm2, respectively.
Optica Applicata, Vol. 53, 2023, nr 1, s. 99-109
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; full subtractor; nonlinear ring resonator; optical Kerr effect; photonic crystal